Study of total antioxidant status and glutathione peroxidase activity in Tunisian vitiligo patients - Jalel Akrem; Hamdaoui Mohamed (Wolters Kluwer Medknow Publications, 2009)
Background: Vitiligo affects one to two percent of the word population. Its pathogenesis has not been clarified yet. Multiple mechanisms such as autoimmune, neuronal, endocrine and oxidative stress resulting from unbalanced antioxidant defense system have been proposed. Aims: Our purpose was to study the total antioxidant status and glutathione peroxidase activity in Tunisian vitiligo patients with or without diabetes or dysthyroidism. Materials and Methods: We studied 60 vitiligo patients and 62 healthy controls. The sex ratio male/female in vitiligo patients was (27/33 = 0.81). Patients with vitiligo were divided into three groups, according to the association with diabetes or dysthyroidism. The total antioxidant status (TAS), glutathione peroxidase activity (GPX activity) was evaluated by adaptable methods using Kits. Results and Conclusion: The generalized vitiligo was the most frequent type (35 patients versus 25 of focal ones). All patients having vitiligo showed low levels of TAS: 0.85 ± 0.7 and low GPX activity: 45 ± 0.6, as compared to the control group: 1.40 ± 0.12 mmol/L; 49 ± 1.8 U/L, (p < 0.01), for TAS and GPX, respectively. The association of low TAS and GPX activities was more pronounced in diabetic vitiligo patients than in dysthyroid vitiligo patients. This study demonstrated that antioxidant processes depletion (low TAS and low GPX activity) is clearly involved with vitiligo in Tunisian patients, regardless of the association of the disease with diabetes or dysthyroidism.